2009
DOI: 10.1021/jm900224r
|View full text |Cite
|
Sign up to set email alerts
|

Improved Peptide Prodrugs of 5-ALA for PDT: Rationalization of Cellular Accumulation and Protoporphyrin IX Production by Direct Determination of Cellular Prodrug Uptake and Prodrug Metabolization

Abstract: Twenty-seven dipeptide derivatives of general structure Ac-Xaa-ALA-OR were synthesized as potential prodrugs for 5-aminolaevulinic acid-based photodynamic therapy (ALA-PDT). Xaa is an alpha-amino acid, chosen to provide a prodrug with appropriately tailored lipophilicity and water solubility. Although no simple correlation is observed between downstream production of protoporphyrin IX (PpIX) in PAM212 keratinocytes and HPLC-derived descriptors of compound lipophilicity, quantification of prodrug uptake reveals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…29,30 Although different strategies have been employed in order to protect the 5-amino group of 5-ALA while keeping some pharmacological activity, they did not really provide any promising candidates for further development. 31,32 Our approach to protect the amino group in 5-ALA from degradation by integration of phosphatase-sensitive moieties aims at providing the stability needed for the systemic administration of 5-ALA whilst keeping the toxicity profile low. As it was previously reported, both protease-sensitive prodrugs are better tolerated in chick embryos than ALA-Hex.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Although different strategies have been employed in order to protect the 5-amino group of 5-ALA while keeping some pharmacological activity, they did not really provide any promising candidates for further development. 31,32 Our approach to protect the amino group in 5-ALA from degradation by integration of phosphatase-sensitive moieties aims at providing the stability needed for the systemic administration of 5-ALA whilst keeping the toxicity profile low. As it was previously reported, both protease-sensitive prodrugs are better tolerated in chick embryos than ALA-Hex.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we have shown that both Ac-Phe-ALA-Me and Ac-Leu-ALA-Me penetrate PAM212 cells more easily than ALA itself (38,40) and that ALA dipeptides entry to the cells is partly driven by passive transport, whereas He-ALA, which is more lipophilic, penetrates mainly through passive diffusion (40).…”
Section: Discussionmentioning
confidence: 94%
“…It has been previously shown that Ac-Phe-ALA-Me and Ac-Leu-ALA-Me are efficient at inducing PpIX in PAM212 cells and in pig skin explants (38,40). N-acetyl termination appears to play an important role in metabolic processes leading to the production of PpIX from such compounds, whereas masking the C-terminus as a methyl ester does not exert a major effect (40).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations